Contribution à l'évaluation de la vitesse d'érosion des cirques glaciaires de quelques massifs anciens européens - Francis Huguet (Physio-Géo)
Morphometric data from a sample of thirty glacial cirques located in European basement regions (Black Forest, South-West Ireland and Wales) assess the rate of glacial erosion. The height of the wall, measured from the summit down to the floor, indicates a value of the average rate of erosion, on condition that the hollow was not partly inherited from the pre-glacial topography (such as structural basins or erosion scarps). Admitting that the mechanical erosion due to the glacier was at work during the cumulated time of all the cold periods since 2.5 MA, that is during about 1.8 MA, and admitting that the lowering of the floor during the Interglacial periods can be neglected, the average rate of glacial erosion can be estimated, ranging from 0.07 to 0.34 mm per year. These values are one order of magnitude smaller than the published data obtained by in situ measuring or calculated from the sediment volumes. If the glacial deepening was achieved during one glacial period only, the estimated values would be twenty times higher, in line with published values.